The effect of group counseling on hope with diverse undergraduates during sustainability-focused internship - Spinks, Hailey; Hannon, Michael D.; Murray, Matthew; Goodey, Nina M.; Billings, Lora; Tuininga, Amy (Frontiers in Education, 2025)
Many adolescents report feeling overwhelmed, depressed, anxious, and hopeless in the face of global climate change. These feelings are both valid and antithetical to the necessary hope and courage it takes to address real-world environmental crises and contribute to meaningful societal impact. The Green Teams Program, an internship-based experiential learning initiative, prepares young professionals with skills and knowledge needed to address these challenges and provides an intentionally inclusive and safe environment for students from all backgrounds to do so. This structured environment includes psychoeducational group counseling among other supports. Intern self-assessments revealed significant gains in measures of Hope, Agency, and Self-Clarity, likely attributed to the Program's intentional and inclusive pedagogical practices. Results from a pre-and post-program assessment instrument, the Hope Action Inventory, indicated that participation in the Green Teams Program impacted individuals' hope for the future and their ability to implement this hope into tangible steps toward their career development. The findings will inform and enhance existing and future STEM-focused experiential learning programs so that students from all backgrounds are well-supported to address the global challenges that impact their generations most.